PICTURE STRIP STORY TECHNIQUE TO IMPROVE STUDENTS' SPEAKING ABILITY - Adzani Oktoisya Arya, Adzani (2020)
This study was aimed to investigate the outcomes of implementing picture strip story technique in narrative speaking and discover students' responses toward the implementation of picture strip story technique itself. The participants of this study were 32 students of one class in junior high school in Bandung. One group pre-test post-test was implemented as a research design. The data were collected by using two instruments; speaking assessment namely pre-test (before treatment) and post-test (after treatment) and students' interview. The results of the study showed that picture strip story technique has successfully improved ninth graders speaking ability which can be seen from the progress of decreasing students' speaking problems. The students' mean score of speaking assessment also increased from 72.28 in pre-test to 78.81 in post-test. In addition, based on the result of interview, the students showed positive and negative responses toward the implementation of picture strip story technique in learning narrative speaking. Keywords: Picture Strip Story Technique, Speaking Ability, Narrative Text. Penelitian ini bertujuan untuk menyelidiki hasil penerapan teknik cerita strip bergambar dalam berbicara naratif dan menemukan respon siswa terhadap penerapan teknik cerita strip bergambar itu sendiri. Partisipan penelitian ini adalah 32 siswa dari satu kelas di SMP di Bandung. Satu kelompok pre-test post-test diimplementasikan sebagai desain penelitian. Data dikumpulkan dengan menggunakan dua instrumen; penilaian berbicara yaitu pre-test dan post-test dan wawancara siswa. Hasil penelitian menunjukkan bahwa teknik cerita strip bergambar telah berhasil meningkatkan kemampuan berbicara siswa kelas sembilan yang dapat dilihat dari penurunan masalah berbicara siswa. Nilai rata-rata siswa dalam penilaian berbicara juga meningkat dari 72,28 pada pre-test menjadi 78,81 pada post-test. Selain itu, berdasarkan hasil wawancara, siswa menunjukkan respon positif dan negatif terhadap penerapan teknik cerita bergambar dalam pembelajaran berbicara naratif. Keywords: Teknik Cerita Strip Bergambar, Kemampuan Berbicara, Teks Naratif.